PENGARUH KARAKTERISTIK SOSIODEMOGRAFI TERHADAP SELF EFFICACY PEREMPUAN KELUARGA MISKIN DALAM MELAKSANAKAN USAHA EKONOMI PRODUKTIF DI SURAKARTA - Suminah Suminah; Sunarru Samsi Hariadi; Sri Widodo; Sri Peni Wastutiningsih (Universitas Sebelas Maret, 2014)
This study aimed to analyze the influence of sociodemographic characteristics to the self-efficacy on women of poor households (WPH) in implementing economically productive activities. The study was conducted at Surakarta, using a survey approach. Samples were taken by multistage random sampling technique. Quantitative data were analyzed using multiple regression models. The results showed that the factors sociodemographic characteristics: age, formal education, and the number of family dependents significant affect on self-efficacy of WPH in conducting productive business at significance level α = 0.10, whereas the non-formal education and long effort had no significant affect. Goodness of fit test results of multiple linear regression model showed that the sociodemographic characteristics collectively have the affect of 28.6 percent.